Complete Genome Sequence of the Newly Developed Lactobacillus acidophilus Strain With Improved Thermal Adaptability - Jeon, Soomin; Kim, Hyaekang; Choi, Youngseok; Cho, Seoae; Seo, Minseok; Kim, Heebal (Frontiers in Microbiology, 2021)
Lactobacillus acidophilus (L. acidophilus) is a representative probiotic and is widely used in many industrial products for its beneficial effects on human and animal health. This bacterium is exposed to harsh environments such as high temperatures for manufacturing industrial products, but cell yield under high temperatures is relatively low. To resolve this issue, we developed a new L. acidophilus strain with improved heat resistance while retaining the existing beneficial properties through the adaptive laboratory evolution (ALE) method. The newly developed strain, L. acidophilus EG008, has improved the existing limit of thermal resistance from 65°C to 75°C. Furthermore, we performed whole-genome sequencing and comparative genome analysis of wild-type and EG008 strains to unravel the molecular mechanism of improved heat resistance. Interestingly, only two single-nucleotide polymorphisms (SNPs) were different compared to the L. acidophilus wild-type. We identified that one of these SNPs is a non-synonymous SNP capable of altering the structure of MurD protein through the 435th amino acid change from serine to threonine. We believe that these results will directly contribute to any industrial field where L. acidophilus is applied. In addition, these results make a step forward in understanding the molecular mechanisms of lactic acid bacteria evolution under extreme conditions.